Radio and optical investigations of storm time evolution of post-midnight equatorial plasma bubbles (EPBs) and their drifts over Indian sector - Gurav, O. B.; Sripathi, S.; Ghodpage, R.N. (My University, 2020)
We investigated the spatio-temporal evolution of disturbed time post mid-night Equatorial Plasma Bubbles (EPBs) using Canadian Advanced Digital Ionosonde (CADI) located at dip equatorial station, Tirunelveli (8.73 N, 77.7 E, 0.23 N Dip. Lat.), an all-sky imager (ASI) observations at low latitude station Panhala (16.48 N, 74.6 E, 11.1 N Dip. Lat.) and Gadanki Ionospheric Radar Interferometer (GIRI) at Gadanki (13.5 N, 79.2 E; 6.5 N Dip. Lat.) which is situated at few degrees towards east and south of Panhala on 02–03 Febru ary 2017 night. During this night, IMF Bz showed its periodic variation starting from 16:00 UT to 23:00 UT accompanied by decrease in SYM-H to as low as 35 nT indicating the onset of weak magnetic storm. The analyzed results suggested that cause of post-midnight EPBs could be due to manifestation of fluctuating eastward/westward electric field due to combined under-shielding/over-shielding Elec tric Fields and disturbance dynamo electric fields that led to rise and fall of the F-layer over dip equator. Interestingly, the EPBs over Panhala showed eastward motion initially that quickly reversed to westward later. Along with westward motion they also started grow ing until 21:30 UT. However, most of these EPBs disappeared with time except the one that started descending/shrinking towards south ern side (i.e. towards equator). The rising and shrinking of EPBs is found to be fairly correlated with the equatorial vertical drifts. The westward drift of EPBs at Panhala and its anti-correlation with vertical drifts has been confirmed from CADI zonal/vertical drifts. Accordingly, the study also investigated the role of storm induced vertical Hall electric field as a possible cause for westward drifts and its anti-correlation with vertical drifts. However, GIRI observations do not show any significant westward drift on this night at Gadanki suggesting that there is a longitudinal gradient in the zonal drift of these EPBs. In addition to longitudinal drift reversal, the latitudinal gradient in zonal drifts also has been noticed. The present work highlights the role of storm induced disturbances in the generation and evolution of post-midnight EPBs which is believed to be triggered by weak magnetic disturbances in the deep low solar minimum.
Keywords: Geomagnetic storm; Equatorial Plasma Bubbles; EPBs; Shrinking of EPBs